Behavioral Consequences of Hawking in Selected Cities in Nigeria - Sandra, Ikenyei N.; Julie, Akpotor (International Journal of Psychosocial Rehabilitation, 2020)
While other social issues enjoy the attention of researchers and policymakers, hawking with its numerous hazardsis given little or no attention. The endemic problem makes many hawkers withdraw, some are discouraged. This leaves the poor hawkers in abject poverty and hunger. This paper examined the hazards of hawking in some selected communities and possible solutions. Weber’s social action theory provided the framework for explanations. For manageability, Nigeria was purposively chosen as a case study. From the three major tribes that make up Nigeria Igbo, Hausa and Yoruba, a total of 280 participants were randomly selected: Ore (70), Benin (70), Onitsha (70), and Abuja (70). 40 in-depth interviews with hawkers were conducted. Quantitative data were analyzed using chi-square and simple percentage. Qualitative data were content analyzed.It was revealed that hawking hazards ranged from kidnapping, physical assault, sexual molestation, robbery, death and gang starism. The research concludes that irrespective of the numerous challenges, many people chose hawking as a means of livelihood to survive hardship. Solutions ranged from the building of stores, socialization to the stationing of mobile policemen around hawking spots.